1974
DOI: 10.1128/iai.9.6.1028-1032.1974
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Acute Otitis Media in Children I. Serotypes Isolated and Serum and Middle Ear Fluid Antibody in Pneumococcal Otitis Media

Abstract: Seventy percent of pneumococci isolated from the middle-ear cavity of infants and children with acute otitis media were of one of the seven serotypes 1, 3, 6, 14, 18, 19, or 23. The immunological response in the serum and middle-ear fluid from otitis media caused by one of these serotypes was studied in 61 children by using either indirect hemagglutination or indirect fluorescent antibody tests, or both. Twenty-six of the patients had pneumococcal antibody present in the acute serum and 28 had it in the conval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(15 citation statements)
references
References 8 publications
(11 reference statements)
3
12
0
Order By: Relevance
“…An immune response to a pathogen traditionally follows infection. In the case of otitis media, nontypeable H. influenzae and S. pneumoniae are often associated with a rise in antibody level during convalescence (12,18,21,22,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…An immune response to a pathogen traditionally follows infection. In the case of otitis media, nontypeable H. influenzae and S. pneumoniae are often associated with a rise in antibody level during convalescence (12,18,21,22,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Most cases resolve spontaneously and the appropriate antibody responses are required for resolution of acute otitis media. 16 IgG immunoglobulins have four subclasses and have been studied more extensively. IgG 2 provides the dominant response to polysaccharide antigens in the circulation and probably the tissues.…”
mentioning
confidence: 99%
“…A possibility that should be borne in mind is that specific antibodies may not produce sufficient opsonization of the pneumococcus (Fc-opsonization) . Shyer et al (26) showed that the presence of type specific antibodies 14 in the middle ear fluid did not prevent development of acute pneumococcal otitis media. We did not study the antibodies in such fluid, but despite type specific antibodies in serum acute pneumococcal otitis media relapsed.…”
Section: Discussionmentioning
confidence: 99%
“…Titers of specific pneumococcal polysaccharide antibodies were determined with the indirect immunofluorescens technique with the use of F I T C labelled anti-human IgG and anti-human IgM antisera (BBL, Division of Becton, Dickinson and Company, USA) as described by Sloyer et al (26).…”
Section: Specific Pneumococcal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation